Endogenous IL-10 Maintains Immune Tolerance but IL-10 Gene Transfer Exacerbates Autoimmune Cholangitis - Hsueh, Yu-Hsin (J Autoimmun, 2018)
The immunomodulatory effect of IL-10 as an immunosuppressive and anti-inflammatory cytokine is well known. Taking advantage of our established mouse model of autoimmune cholangitis using 2-octynoic acid conjugated ovalbumin (2-OA-OVA) induction, we compared liver pathology, immune cell populations and antimitochondrial antibodies between IL-10 knockout and wild type mice immunized with 2-OA-OVA. At 10 weeks post immunization, portal inflammation and fibrosis were more severe in 2-OA-OVA immunized IL-10 knockout mice than in wild type mice. This was accompanied by significant higher levels of collagen I and III expression, T, NK and NKT subsets in liver and IgG anti-mitochondrial autoantibodies (AMA) compared to 2-OA-OVA immunized wild type mice, suggesting that endogenous IL-10 is necessary for the maintenance of immune tolerance in primary biliary cholangitis (PBC). Further, we investigated whether administration of exogenous IL-10 could prevent PBC by administration of IL-10 expressing recombinant adeno-associated virus (AAV-IL-10) either 3 days before or 3 weeks after the establishment of liver pathology. Interestingly, administration of AAV-IL-10 resulted in increased liver inflammation and fibrosis, accompanied by increases in IFN-γ in liver CD4(+) T cell, granzyme B, FasL, and CD107a in liver CD8(+) T and NKT cells, and granzyme B and FasL in liver NK cells of AAV-IL-10 administered mice compared with control mice. Furthermore, administration of AAV-IL-10 significantly increased levels of proinflammatory cytokines and chemokines (IFN-γ, TNF-α, CXCL9 and CXCL10) and collagen I and III production in naive mice, together with increase in immune cell infiltration and collagen deposition in the liver, suggesting a role of IL-10 in fibrosis. In conclusion, our data demonstrate that endogenous IL-10 is critical in the maintenance of immune tolerance but exogenous administration of IL-10 exacerbates liver inflammation and fibrosis. Furthermore, the distinctive presence of inflammatory immune cell populations and collagen expression in AAV-IL-10 treated naive mice cautions against the clinical use of exogenous IL-10 in patients with autoimmune cholangitis.